If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 7 = -2 + -4x Reorder the terms: 7 + 5x = -2 + -4x Solving 7 + 5x = -2 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. 7 + 5x + 4x = -2 + -4x + 4x Combine like terms: 5x + 4x = 9x 7 + 9x = -2 + -4x + 4x Combine like terms: -4x + 4x = 0 7 + 9x = -2 + 0 7 + 9x = -2 Add '-7' to each side of the equation. 7 + -7 + 9x = -2 + -7 Combine like terms: 7 + -7 = 0 0 + 9x = -2 + -7 9x = -2 + -7 Combine like terms: -2 + -7 = -9 9x = -9 Divide each side by '9'. x = -1 Simplifying x = -1
| m/9=25/m | | 4+3i/5+5i | | -1+2*-2=Y | | 4x=204 | | -6/7(4t+6)=3/28t-11 | | 3/8=21/(t+4) | | 7-45z=5z+13 | | -2y+2=20 | | -21y+14=24y+-16 | | 4(12-u)/5=-4u+12 | | 24x+3=24 | | -8(3a-9)=0 | | y=-1/2*-2+2 | | (13x+45)+(19x+3)=180 | | -29+10y+7=3(4y-2)-4 | | 180-.14x=.29x | | 2(9x+7)-6x=3(4x+2)-9 | | 4x+7+2x=5 | | 2(1+x)/3=x+1 | | y=-1/2*-4+2 | | 180-.14=.29 | | 3x+7+x+8=39 | | 7/2x+1/2=27.5+9/2x | | -14=2(2x+3) | | 22x+7-27x=1-9 | | 16-x=4(4-3x) | | 6-5*3=y | | 3+4x=-3x+87 | | 7x+15-6x=-5-12 | | 6-5*2=y | | -18=3(y+1) | | -7x+7x=-x |